2007
DOI: 10.5194/hess-11-1417-2007
|View full text |Cite
|
Sign up to set email alerts
|

A multimodel ensemble approach to assessment of climate change impacts on the hydrology and water resources of the Colorado River Basin

Abstract: Abstract. Implications of 21st century climate change on the hydrology and water resources of the Colorado River Basin were assessed using a multimodel ensemble approach in which downscaled and bias corrected output from 11 General Circulation Models (GCMs) was used to drive macroscale hydrology and water resources models. Downscaled climate scenarios (ensembles) were used as forcings to the Variable Infiltration Capacity (VIC) macroscale hydrology model, which in turn forced the Colorado River Reservoir Model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
311
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 498 publications
(341 citation statements)
references
References 24 publications
12
311
0
6
Order By: Relevance
“…Climate change in the CRB is anticipated to cause large impacts to water resource sustainability (Christensen and Lettenmaier, 2007;Rasmussen et al, 2014;Dawadi and Ahmad, 2012). However, to our knowledge, few modeling studies have considered the impacts of climate change coupled with changes in vegetation (Buma and Livneh, 2015;Carroll et al, 2017;Pribulick et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Climate change in the CRB is anticipated to cause large impacts to water resource sustainability (Christensen and Lettenmaier, 2007;Rasmussen et al, 2014;Dawadi and Ahmad, 2012). However, to our knowledge, few modeling studies have considered the impacts of climate change coupled with changes in vegetation (Buma and Livneh, 2015;Carroll et al, 2017;Pribulick et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…En la primera década del siglo xxi se llegó a los niveles más bajos de reservas en las presas. Los modelos a largo plazo, algunos para el 2050, otros para el 2100, indican que se dará un incremento en la temperatura de la cuenca de 1.8º a 4.5º centígrados (Christensen y Lettenmaier, 2006). Por otra parte, las proyecciones de crecimiento de la población para todas las entidades de la cuenca indican que en los próximos años las tensiones para el abasto urbano se incrementarán notablemente (Nowak, Hoerling, Rajagopalan y Zagona, 2012).…”
Section: Un Escenario Sobre La Variabilidad En El Año 2009unclassified
“…Dado que supuestamente no se realizó dicha definición, ante las prospectivas de un siglo xxi seco (Cook, Ault y Smerdon, 2015) el tema se vuelve importante en función de una necesaria cooperación binacional. Ante ello se han generado gran cantidad de textos con el fin de que ambos países propicien medidas alternativas ante una condición de la naturaleza que parece irremediable: el cambio climático y sus consecuencias en los procesos productivos, el abasto urbano, la producción de energía eléctrica, la pesca y su relación con la conservación del medio ambiente (Christensen y Lettenmaier, 2006). En diferentes medios de comunicación se ha establecido un vínculo que conlleva a una relación que consideramos debe ser matizada: la variabilidad del flujo del río Colorado se debe al cambio climático.…”
Section: Introductionunclassified
“…In addition, climate change may even be speeded up in the future, consequently leading to an increase in probabilities of floods and droughts. Therefore, changes in water resources and the underlying driving forces due to climate changes have become research focuses (Andréasson et al, 2004;Christensen and Lettenmaier, 2007;Frederick and Major, 1997;Gül et al, 2010;Lins and Slack, 1999;Liu and Cui, 2009;Null et al, 2010;Piao et al, 2007;Thodsen, 2007;Vörösmarty et al, 2000;Xu et al, 2010;Zhang et al, 2001). Andréasson et al (2004) discussed the impacts of climate change on streamflow under three anthropogenic CO 2 emission scenarios with a hydrology model (HBV) and concluded that the influences of climate change based on hydrology cycle varied geographically.…”
Section: S L Sun Et Al: Past and Future Changes Of Streamflow In Pmentioning
confidence: 99%